The Time Series Evaluation of Land Use Suitability Using GIS: A Case Study ofthe Detailed Spatial Plan in Prambanan, Sleman Regency - Suprojo, Baskara; Muhammad, Abid (Jurnal Geografi : Media Informasi Pengembangan dan Profesi Kegeografian, 2024)
Land use is a management practice carried out by humans to optimize the results of natural resources that support multi-sector activities. One of the changes in land use comes from the tourism sector, which is utilized by the community and can have both positive and negative impacts. Prambanan District, which is part of Sleman Regency, is designated as an area for cultural heritage tourism and sustainable agriculture. This study aims to determine changes in land use over time and their compliance with applicable spatial regulations. A mixed method is used in this research: quantitative for land use changes over time and compliance with the Detailed Spatial Plan (RDTR), and qualitative regarding the causes and efforts to align land use changes with applicable spatial regulations. The results show that there are land use changes that have increased, decreased, and remained stagnant from 2022-2024. Land use compliance from 2022-2024 with the Detailed Spatial Plan zoning regulations shows 84% permitted, 1% limited permission, 5% conditional permission, and 10% not permitted. The causes of land use changes and non-compliance with the Detailed Spatial Plan are due to human needs in various sectors. Efforts have been made by the government through spatial regulations and sustainable farmer programs. The implementation of spatial analysis in examining land use changes over time and evaluating compliance with spatial regulations can serve as a reference for other regions.